Dirāsah Muqāranah li Natījah al-Ta‘allum fī ‘Ilm al-Naḥw baina Ṭalabah Barnāmij al-I‘dād al-Lugawī fī Jâmi‘At Magfirah wa Jâmi‘At Al-Râyah: Dirâsah Muqâranah bi Manhaj Kammiy: دراسة مقارنة لنتيجة التعلم في علم النحو بين طلبة برنامج الإعداد اللغوي في جامعة مغفرة وجامعة الراية دراسة مقارنة بمنهج كمي - Adi Budiman (Institut Muslim Cendekia, 2026)
This study investigates significant differences in grammatical achievement between language preparation students at Maghfirah (STIPI) and Istitut Muslim Cendikia (IMC), Indonesia and explain the reasons for the differences in learning outcomes between the two. This research a quantitative approach, a sample of 110 students (56 from STIPI and 54 from IMC) was selected through purposive. Data were collected via a 31-item objective achievement test, which demonstrated high reliability. Due to non-normal distribution, the Mann-Whitney U test was employed for analysis using SPSS. The results revealed a statistically significant difference (Sig = 0.000) favoring IMC with an average to large effect size of r = 0.399. IMC students achieved a high mean score of 84,40, while STIPI students scored 69.00. This disparity is attributed to two primary factors: academic, namely higher weekly study hours at IMC (4-5 hours) compared to STIPI (2-3 hours); and environmental, specifically IMC’s